guys,solve this plzzz.......
Attachments:
![](https://hi-static.z-dn.net/files/db9/aecb79977a1c394be13f55643b95c2f8.jpg)
Answers
Answered by
2
if a,b,c are in AP,
b-a = c-b
to prove 1/bc, 1/ca, 1/ab are in AP, we need to show 1/ca - 1/bc = 1/ab - 1/ca
LHS:
1/ca - 1/bc = (b-a)/abc
RHS:
1/ab - 1/ca = (c-b)/abc
but we know that (b-a) = (c-b)
thus LHS = RHS.
Hence 1/bc, 1/ca, 1/ab are in AP.
Note: Calculation of 1/ca - 1/bc
You need to first take the LCM of ca and bc which is abc and do the calculation. I have calculated like this above.
Or
\frac{1}{ca} - \frac{1}{bc} = \frac{bc-ca}{abc^{2}} = \frac{c(b-a))}{abc^{2}} = \frac{b-a}{abc}ca1−bc1=abc2bc−ca=abc2c(b−a))=abcb−a
Here instead of taking LCM, i have multiplied the terms, which is fine. You will get the same answer.
b-a = c-b
to prove 1/bc, 1/ca, 1/ab are in AP, we need to show 1/ca - 1/bc = 1/ab - 1/ca
LHS:
1/ca - 1/bc = (b-a)/abc
RHS:
1/ab - 1/ca = (c-b)/abc
but we know that (b-a) = (c-b)
thus LHS = RHS.
Hence 1/bc, 1/ca, 1/ab are in AP.
Note: Calculation of 1/ca - 1/bc
You need to first take the LCM of ca and bc which is abc and do the calculation. I have calculated like this above.
Or
\frac{1}{ca} - \frac{1}{bc} = \frac{bc-ca}{abc^{2}} = \frac{c(b-a))}{abc^{2}} = \frac{b-a}{abc}ca1−bc1=abc2bc−ca=abc2c(b−a))=abcb−a
Here instead of taking LCM, i have multiplied the terms, which is fine. You will get the same answer.
Answered by
1
If a, b, c are in AP.
Then,
b-a = c-b = common difference
2b = c+a
b = (c+a)/2
Let's substitute this value of b in the next AP series,
which are,
![\frac{1}{bc} , \frac{1}{ac} , \frac{1}{ab} \frac{1}{bc} , \frac{1}{ac} , \frac{1}{ab}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bbc%7D+%2C+%5Cfrac%7B1%7D%7Bac%7D+%2C+%5Cfrac%7B1%7D%7Bab%7D+)
which after substitution will become,
![\frac{2}{(c + a)c} , \frac{1}{ca}, \frac{2}{a(a + c)} \frac{2}{(c + a)c} , \frac{1}{ca}, \frac{2}{a(a + c)}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B%28c+%2B+a%29c%7D+%2C+%5Cfrac%7B1%7D%7Bca%7D%2C+%5Cfrac%7B2%7D%7Ba%28a+%2B+c%29%7D+)
Now if the 2nd term - 1st term = 3rd term -2nd term.
Then this series is in AP.
Let's check that,
![\frac{1}{ca} - \frac{2}{c(a + c)} \\ = \frac{c(a + c) - 2ac}{a {c}^{2}(a + c) } \\ = \frac{ {c}^{2} - ac }{a {c}^{2} (a + c)} \\ \frac{c(c - a)}{a {c}^{2} (a + c)} = \frac{ - 1}{ac} \frac{1}{ca} - \frac{2}{c(a + c)} \\ = \frac{c(a + c) - 2ac}{a {c}^{2}(a + c) } \\ = \frac{ {c}^{2} - ac }{a {c}^{2} (a + c)} \\ \frac{c(c - a)}{a {c}^{2} (a + c)} = \frac{ - 1}{ac}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7Bca%7D++-++%5Cfrac%7B2%7D%7Bc%28a+%2B+c%29%7D++%5C%5C++%3D++%5Cfrac%7Bc%28a+%2B+c%29+-+2ac%7D%7Ba+%7Bc%7D%5E%7B2%7D%28a+%2B+c%29+%7D++%5C%5C++%3D++%5Cfrac%7B+%7Bc%7D%5E%7B2%7D+-+ac+%7D%7Ba+%7Bc%7D%5E%7B2%7D+%28a+%2B+c%29%7D+%5C%5C++%5Cfrac%7Bc%28c+-+a%29%7D%7Ba+%7Bc%7D%5E%7B2%7D+%28a+%2B+c%29%7D+++%3D++%5Cfrac%7B+-+1%7D%7Bac%7D+)
Similarly,
![\frac{2}{a(a + c)} - \frac{1}{ac} \\ = \frac{ - 1}{ac} \frac{2}{a(a + c)} - \frac{1}{ac} \\ = \frac{ - 1}{ac}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7Ba%28a+%2B+c%29%7D++-++%5Cfrac%7B1%7D%7Bac%7D++%5C%5C++%3D++%5Cfrac%7B+-+1%7D%7Bac%7D+)
The common difference here is constant.
Hence, It's in AP.
Then,
b-a = c-b = common difference
2b = c+a
b = (c+a)/2
Let's substitute this value of b in the next AP series,
which are,
which after substitution will become,
Now if the 2nd term - 1st term = 3rd term -2nd term.
Then this series is in AP.
Let's check that,
Similarly,
The common difference here is constant.
Hence, It's in AP.
Similar questions